PRESERVATION OF HOT CHILI WITH ACTIVATED NATURAL ZEOLITE - Fatimah, Dewi; Estiaty, Lenny M. (Jurnal Zeolit Indonesia, 2003)
Investigation has been done for chilli (keriting and hot beauty type) preservation using natural silicate (zeolite). Zeolite from Cikancra (mordenite and clinoptilolite type is prepared in various particle sizes and activated at different temperatures. The activated zeolite is tested for its ability to absorb water. It is found that zeolite with particle size of -100 +140 mesh and activated at 400ÂºC has the highest capability for water absorption. This zeolite is then used in the preservation tests. Zeolite can extend the preservation of chillies up to 18 days for âhot beautyâ type and 23 days for âkeritingâ type. Vitamin C plus (Vit.C + organics) content of chillies after preservation is also increased to 378.29 mg/100g (keriting) and 606.87 mg/100g for hot beauty. During preservation period, pH of hot beauty chilli is constant while pH of keriting chilli is decreased from 5.66 to 5.39. Carbohydrate content is increased for keriting chilli from 2.18% to 2.33% but it is decreased for hot beauty chilli from 2.77% to 2.01%. Total soluble solid (TSS) content of both chillies is decreased to below 0.95%. Water content of fresh chillies, for keriting type is 79.73% and for hot beauty type is 88.40%. Unexpectedly, fungiâs are formed in small parts of chillies during preservation. However, in general, the preservation tests in closed system have produced fresh chillies with high nutrition content.